At the age of 75. Photo on an illustrated page in "Forwerts" on the occasion of the 90th birthday of the "Grandmother of the Russian revolution"
At the age of 75. Photo on an illustrated page in "Forwerts" on the occasion of the 90th birthday of the "Grandmother of the Russian revolution".